Performance of tissuecultured versus suckerderived East African highland banana (Musa AAAEA) under high and low input systems in Uganda - Niere, B.; Gold, C.; Coyne, Danny L.; Dubois, T.; Sikora, R.A. (Elsevier, 2014)
Banana (Musa spp.) is a vegatatively propagated crop and the type of planting material is of great importancefor the productivity of banana plantations. Traditionally, sucker derived planting materials havebeen used to establish banana plantations but there is a risk of transmitting pests such as plant-parasiticnematodes with untreated suckers. Tissue cultured banana plants are pest-free and widely grown incommercial dessert banana plantations but are not common agricultural practice under East Africanconditions. This study aimed at evaluating the agronomic performance and nematode infestation levelsof sucker-derived and tissue cultured planting material of the East African highland cooking bananacultivar Nabusa (Musa spp., genome group AAA-EA) over five crop cycles. A field trial was conductedin Central Uganda using tissue culture plants, untreated suckers, pared suckers or pared and hot watertreated suckers.All plants were cultivated under mulched or non-mulched conditions to represent high or low inputsystems, respectively. Mulch in general improved agronomic performance of banana. Type of plantingmaterial also influenced plant growth and yield. Tissue culture plants developed faster and yielded higherduring the first crop cycle than sucker-derived material but not thereafter. Plant height and bunch weightof untreated suckers was inferior to all other planting material from the third crop cycle onwards. Allmulched plants flowered earlier in all crop cycles. Duration from planting to the first harvest was lessfor tissue-cultured plants, but planting material had no influence on days to harvest from the third cropcycle onwards. Nematode densities were higher in roots from plants grown from untreated suckersthan all other planting material, with Radopholus similis consistently recovered in greater densities thanHelicotylenchus multicinctus across treatments. Mulching had no influence on nematode densities, rootnecrosis, number of root base lesions or number of dead roots. Nematode associated damage was higherin plants from untreated suckers but did not differ among tissue-cultured and pared and hot water treatedor pared sucker plants. This study demonstrates the benefits of using clean planting material for cookingbanana over five consecutive crop cycles and confirms the beneficial effects of mulching. In order toachieve high banana yields over several crop cycles, clean planting material needs to be supported bythe application of mulch. However, this study shows that the application of mulch will not offset thedetrimental effects of plant parasitic nematode-infected sucker planting material.